2014
DOI: 10.1021/ml4004843
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing a CH−π Interaction to Increase the Affinity for 5-HT1A Receptors

Abstract: An electrostatic interaction related to a favorable position of the distal phenyl ring and a phenylalanine residue in the binding pocket would explain the higher 5-HT 1A affinity of a 4-phenyl-1,2,3,6-tetrahydropyridine (THP) analogue compared to the corresponding 4-phenylpiperazine analogue. To explore a possible reinforcement of this interaction to increase the affinity for 5-HT 1A receptors, different 4-substituted-phenyl analogues were synthesized and tested. The most important increase of affinity is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The obtained model was verified to have all the amino acid residues implied in the binding of various agonists and antagonists in the binding pocket as well as appropriate distances between crucial residues, in accordance with previous studies. 17,18 All ligands have been prepared manually in Maestro (Maestro, Schrödinger, LLC, New York, NY, 2016). We used LigPrep software (LigPrep, Schrödinger, LLC, New York, NY, 2016.)…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained model was verified to have all the amino acid residues implied in the binding of various agonists and antagonists in the binding pocket as well as appropriate distances between crucial residues, in accordance with previous studies. 17,18 All ligands have been prepared manually in Maestro (Maestro, Schrödinger, LLC, New York, NY, 2016). We used LigPrep software (LigPrep, Schrödinger, LLC, New York, NY, 2016.)…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Additionally, all presented ligand poses exhibit the crucial interaction between the basic nitrogen atom of piperazine and D116, known to play a vital role in the stabilization of the ligands of this class in the binding pocket. 17 Based on the computational results we can try to rationalize the obtained experimental K i values. Fig.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Indeed, as proposed in previous work 39 in the THP analogues, the phenyl ring presents in preference an almost coplanar orientation relative to the THP moiety, which is more favorable for an edge-to-face CH-π interaction with Phe 362 (Phe 6.52). 40 The dihedral angle measured between the ring planes (92°) is very close to the optimal value of 90°. 41 On the contrary, for the piperazine analogue 3, the more perpendicular orientation of the phenyl ring is less favorable for the CH−π interaction with a dihedral angle of 59°.…”
Section: Resultsmentioning
confidence: 55%
“…On full interaction maps of 1 , it is shown that these requirements are fulfilled. Hence, taking into account the model proposed by Kołaczkowski et al [ 14 ], the molecule of 1 in the conformation found in solvates seems to be a good candidate to obey the general affinity hypothesis for interactions with the 5-HT7 receptor, as well as due to additional fragment enhancing C-H…π interactions, it may also be an effective ligand for the 5-HT1a receptor [ 51 ].…”
Section: Discussionmentioning
confidence: 99%